University education academic policies and students` sports talent development in elite sports in the universities in Kenya - Kubai, J. T.; Mwangi, P. W.; Owiti, B. (International Journal of Professional Practice, 2021)
Literature has revealed that United States of America and other European countries associated with monopolization of performance in international sports competitions, like Olympic Games, have collaborated with their universities to nurture talented students pursuing university education. The universities in Kenya have contributed insignificantly to sports` talents development, particularly talents that represent the country in international sports competitions. Education reform in Kenya is phasing out the 8-4-4 curriculum in favor of 2-6-3-3-3 education system. The embraced curriculum has introduced talent pillar on sports as an academic pathway in the education system including universities. This study investigated the nexus between university education and students` sports` talent development in selected universities in Kenya. The objective was to establish the relationship between universities` education academic policies and students` sports talent development. The study was anchored on systems theory, since management of sports in the universities is guided and informed by structured sports management sub-systems. The study employed both qualitative and quantitative methods in a convergent parallel mixed methods design. The tools for collecting data were questionnaires, interview schedules, observation, content analysis and focus group discussion. The response rate was 96.2% of student respondents. The reliability was established through generating Crobanch`s alpha coefficient as 0.714. Cross tabulation methods facilitated the testing of the null hypothesis; (H01). The hypothesis was rejected, Chi2 (16) = 97.397, p = 0.05 implying a significant relationship between implementation of university academic policies and students` talent development in elite sports in the universities in Kenya. However, Cramer`s V (0.253) and Pearson, R (-0.004) respectively revealed that the relationship was moderate and inverse. The findings of the study revealed that current university policies emphasize on academics and not talent development. The study recommended that university academic polices be revised to increase the strength and change the direction of the relationship.